HUBUNGAN PENGETAHUAN IBU TENTANG IMUNISASI PNEUMOKOKUS KONYUGASI VAKSIN DENGAN STATUS IMUNISASI PNEUMOKOKUS KONYUGASI VAKSIN PADA ANAK BALITA (1-2 TAHUN) - Ni Luh Ade Widiastuthi,; Listiana Ade Widya Ningtyas,; Ni Nyoman Suindri, (Journal of Innovation Research and Knowledge, 2025)
Pneumonia is a leading cause of death among infants and toddlers worldwide, accounting for 14% of total deaths in this age group. Pneumococcal Conjugate Vaccine (PCV) immunization is a routine program. By 2023, PCV immunization coverage in Selat Village reached 78.95%. This study examines the relationship between mothers' knowledge of PCV immunization and PCV immunization status in toddlers (1–2 years old) in Selat Village. Using a cross-sectional approach, the study was conducted from September to November 2024 with a total sampling technique involving 40 mothers with toddlers aged 1–2 years. Data were collected through questionnaires and verification of children's immunization status in the Maternal and Child Health (MCH) handbook. Data analysis included univariate analysis for frequency distribution and bivariate analysis using the fisher’s exact test with a significance level of p < 0.05. The results showed a p-value = 0.000, indicating a significant relationship between mothers' knowledge and PCV immunization status. Mothers with good knowledge of PCV immunization are more likely to complete their children’s PCV immunization. Health workers should enhance public awareness, and future research should explore other factors affecting PCV immunization status